Is the God of Traditional Theism Logically Compatible with All the Evil in the World? (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Is the God of traditional theism logically incompatible with all the evil in the world? In his book, Is a Good God Logically Possible? (Palgrave paperback, 2019) James Sterba argues that the God of traditional theism is logically incompatible with especially the horrendous evil consequences of moral and natural evil that exists in our world. In this Special Issue in Religions, sixteen philosophers challenge Sterba’s argument and he responds to all of them.